Annual Plan 1995-96 Vol. II Statements Government of Uttar Pradesh - Planning Commission (Planning Commission, 1995)
Departmentwise/Sectorwise Outlay & Expenditure Physical Targets and Achievements Rural Development Special Area Programme Irrigation and Flood Control Energy Industry and Minerals Transport Communication.
Government of Uttar Pradesh